Alan Rudolph's Trouble in Mind Tampering with Myths - Flinn, Caryl (Out of the Archives, 2023)
Despite a career spanning over forty years, filmmaker Alan Rudolph has flown largely under the radar of independent film scholars and enthusiasts, often remembered as Robert Altman's protégé. Through a reading of his 1985 film Trouble in Mind, Caryl Flinn demonstrates that Rudolph is long overdue for critical re-evaluation. Exploring Trouble in Mind's influence on indie filmmaking, Rudolph's dream-like style, and the external political influences of the Reagan era, Flinn effectively conveys the originality of Rudolph's work through this multifaceted film. Utilizing archival materials and interviews with Rudolph himself and his collaborators, Flinn argues for this career-defining film's relevance to American independent cinema and the decade of the 1980s. Amply illustrated with frame enlargements and set photographs, this book uncovers new production stories and reception contexts of a film that Flinn argues deserves a place in the limelight.